2008
DOI: 10.1073/pnas.0711027105
|View full text |Cite
|
Sign up to set email alerts
|

Bardet–Biedl syndrome proteins are required for the localization of G protein-coupled receptors to primary cilia

Abstract: Primary cilia are ubiquitous cellular appendages that provide important yet not well understood sensory and signaling functions. Ciliary dysfunction underlies numerous human genetic disorders. However, the precise defects in cilia function and the basis of disease pathophysiology remain unclear. Here, we report that the proteins disrupted in the human ciliary disorder Bardet-Biedl syndrome (BBS) are required for the localization of G proteincoupled receptors to primary cilia on central neurons. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
423
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 425 publications
(446 citation statements)
references
References 47 publications
14
423
2
Order By: Relevance
“…Seven of the known BBS proteins (BBS1-2, BBS4-5, BBS7-9) have been shown to form a stable complex, the BBSome, and this complex is proposed to function in vesicle trafficking to the ciliary membrane through a Rab8-mediated mechanism (31). Consistent with this, several G-protein-coupled receptors failed to localize to neuronal cilia in Bbs2 and Bbs4 null brains (32). In addition, we have recently demonstrated that one component of the BBSome, BBS1, directly interacts with the leptin receptor and that leptin signaling is attenuated in BBS gene knockout mice, implicating BBS function in a broad range of membrane receptor signaling (33).…”
supporting
confidence: 52%
“…Seven of the known BBS proteins (BBS1-2, BBS4-5, BBS7-9) have been shown to form a stable complex, the BBSome, and this complex is proposed to function in vesicle trafficking to the ciliary membrane through a Rab8-mediated mechanism (31). Consistent with this, several G-protein-coupled receptors failed to localize to neuronal cilia in Bbs2 and Bbs4 null brains (32). In addition, we have recently demonstrated that one component of the BBSome, BBS1, directly interacts with the leptin receptor and that leptin signaling is attenuated in BBS gene knockout mice, implicating BBS function in a broad range of membrane receptor signaling (33).…”
supporting
confidence: 52%
“…BBS proteins are required for proper ciliary localization in neurons of the Mchr1 receptor, involved in regulation of feeding behavior (12). Hypothalamic ciliated neurons may be involved in the leptin resistance recently described in BBS patients and obese BBS knockout mouse models (10,45).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a cardinal feature of the disease, for which the ciliary pathogenesis remains to be clarified (8). The hypothesis of defects in the ciliated central nervous system neurons (9) that regulate fat storage has been explored and has gained recent support from studies of animal models (10)(11)(12). Moreover, as the adipocyte has been described to be a nonciliated cell (13) and is not referenced in the list of ciliated cells (http://www.bowserlab.org/primarycilia/cilialist.html), a direct implication of this cell in the pathogenesis of BBS-associated obesity has, so far, not been investigated.…”
mentioning
confidence: 99%
“…Cilia are microtubule based appendages that extend from the basal bodies of cells and are either motile or immotile [16]. Primary cilia are immotile and are present on almost on all human cell types [17].…”
Section: Bbs Proteins In Ciliary Functionmentioning
confidence: 99%